Performance comparison of fiber reinforced polymer (FRP) systems and textile reinforced mortar (TRM) for concrete confinement at elevated temperature - D. Akhil Varma; Prabir K. Sarker; Mini K. Madhavan; Karingamanna Jayanarayanan (Composites Part C: Open Access, 2025)
Due to the infrastructure development, retrofitting and rehabilitation techniques are gaining momentum in the construction sector. Fiber reinforced polymer and textile reinforced mortar confinement are recognized as promising techniques by the industry. The current study evaluates the effectiveness of Textile Reinforced Mortar (TRM) and Fiber Reinforced Polymer (FRP) systems for confining concrete cylinders under high temperatures, utilizing jute and basalt fibers as reinforcing agents. The confinement efficiencies of TRM hybrid systems were 1.50, 1.46, 1.46 and 1.34 at temperatures of 100 °C, 200 °C, 300 °C, and 400 °C respectively, while for the hybrid FRP system, they were 1.58, 1.47, 1.29 and 1.15 at the same temperatures after 4-hour exposure. The addition of jute fibers in TRM demonstrated a notable enhancement in residual strength, Young's modulus, and failure strain at temperatures reaching 400 °C, whereas basalt fiber-reinforced TRM systems exhibited better thermal and fire resistance. Conversely, FRP systems, which consist of jute and basalt fibers, showed reduced mechanical properties and considerable degradation under high temperatures. The results indicate that TRM systems provide a more efficient and dependable option for concrete confinement applications under high temperatures, especially when jute and basalt fibers are utilized as reinforcement materials. The exceptional efficiency of TRM confinement systems at high temperatures positions them as a viable substitute for conventional FRP confinement systems in structural applications in fire-sensitive environments.